The T-Type Calcium Channel Cav3.2 in Somatostatin Interneurons in Spinal Dorsal Horn Participates in Mechanosensation and Mechanical Allodynia in Mice - Zhi, Yu-Ru; Cao, Feng; Su, Xiao-Jing; Gao, Shu-Wen; Zheng, Hao-Nan; Jiang, Jin-Yan; Su, Li; Liu, Jiao; Wang, Yun; Zhang, Yan; Zhang, Ying (Frontiers in Cellular Neuroscience, 2022)
Somatostatin-positive (SOM+) neurons have been proposed as one of the key populations of excitatory interneurons in the spinal dorsal horn involved in mechanical pain. However, the molecular mechanism for their role in pain modulation remains unknown. Here, we showed that the T-type calcium channel Cav3.2 was highly expressed in spinal SOM+ interneurons. Colocalization of Cacna1h (which codes for Cav3.2) and SOMtdTomato was observed in the in situ hybridization studies. Fluorescence-activated cell sorting of SOMtdTomato cells in spinal dorsal horn also proved a high expression of Cacna1h in SOM+ neurons. Behaviorally, virus-mediated knockdown of Cacna1h in spinal SOM+ neurons reduced the sensitivity to light touch and responsiveness to noxious mechanical stimuli in naïve mice. Furthermore, knockdown of Cacna1h in spinal SOM+ neurons attenuated thermal hyperalgesia and dynamic allodynia in the complete Freund’s adjuvant-induced inflammatory pain model, and reduced both dynamic and static allodynia in a neuropathic pain model of spared nerve injury. Mechanistically, a decrease in the percentage of neurons with Aβ-eEPSCs and Aβ-eAPs in superficial dorsal horn was observed after Cacna1h knockdown in spinal SOM+ neurons. Altogether, our results proved a crucial role of Cav3.2 in spinal SOM+ neurons in mechanosensation under basal conditions and in mechanical allodynia under pathological pain conditions. This work reveals a molecular basis for SOM+ neurons in transmitting mechanical pain and shows a functional role of Cav3.2 in tactile and pain processing at the level of spinal cord in addition to its well-established peripheral role.